High jump drills - Caan, A. F. (The Best of British Track & Field Drills Series, 2009)
Coach Alex "Fuzz" Caan has developed an innovative 7-part drill series to help your high jumpers reach new heights. Caan's high jump drills work on developing a feel or a groove for attaining proper posture on the run up, the technical nuances to assist in injury prevention, strategies for running the curve with the goal of generating "free energy" to take into the jump, take-off positioning, developing timing over the bar without the stress of a full run up, on the flop through body control with spatial awareness and more. In addition, Caan shares several gymnastics skills that can have a very positive carryover into a high jumper's development. With three expert demonstrators, accompanied by Caan's energetic high jump instruction and innovative high jump drills, this instructional DVD is certain to assist you in your high jump coaching.